Software Defined Networking (SDN) Challenges, issues and Solution - Rana, Deepak Singh; Dhondiyal, Shiv Ashish; Chamoli, Sushil Kumar (International Journal of Computer Sciences and Engineering, 2019)
IT infrastructure and its maintenance processes are changing in different organizations by the advent of cloud computing and may be able to eliminate their existing hardware. In traditional way of configuring a switch or routers may error-prone and cannot fully utilize the capability of existing network infrastructure. SDN is a way of providing programmability for network application development by its distinguished features decoupling the control plane from the data plane. In this paper we focused on the new concept in computer networking field, software defined network (SDN) and its challenges, issues, solutions. First, we provided and cover its basic model and software used to build a computer network with the help of software defined network mechanism then software tools used are listed, challenges and issues are described.